Dental anxiety screening practices and self‐reported training needs among Australian dentists. (17th September 2014) - Armfield, JM; Mohan, H; Luzzi, L; Chrisopoulos, S
Abstract Background It is recommended that dentists screen for dental anxiety (DA) so that fearful patients may be better managed. The main aim of this study was to determine what dentists are being taught in relation to DA as well as whether and how anxious patients are identified in the clinic. Methods Two hundred and forty‐six practising dentists (adjusted response rate = 40.1%), from a random sample of registered Australian dentists, completed a mailed questionnaire. Results Dentists estimated that high DA affected 23.3% of children and 19.4% of adults seen. Only 3.7% of dentists reported using a published scale for screening DA, with the most common reason being lack of awareness (56.5%). Approximately one‐half of responding dentists directly asked their patients about DA and this was more common among younger dentists (χ2 = 7.75, p = 0.021). There were few differences in DA screening by other practitioner or practice characteristics (p > 0.05). Only one‐third of dentists had received undergraduate training related to DA and only 41.7% considered this to be 'good' or better. Almost 37% of respondents expressed an interest in future training opportunities. Conclusions The use of formal, validated scales for screening DA is minimal. Training in anxiety management appears to be low and is an area that could be expanded upon.